Profil kesehatan mental mahasiswa psikologi ditinjau dari gender dan tendensi gangguan mental - Aidina, Wenny; Riady, Muhammad Antos; Mirza, Mirza (JOURNAL OF Mental Health Concerns, 2025)
Background: Psychology students are a group that is vulnerable to emotional and psychological stress, both due to academic burden and expectations of future professional roles. More frequent exposure to various mental health issues can contribute to students’ psychological problems. The constant influx of information can overwhelm students and make it difficult for them to cope. Purpose: To identify the mental health profile of psychology students in terms of gender and describe the tendencies of mental disorders that appear in each gender. Method: This comparative quantitative study involved 70 psychology students. Data collection was carried out using Woodworth's Questionnaire instrument. Data were analyzed using an Independent Samples T-Test to examine differences in scores based on gender, along with descriptive statistics. Results: The analysis results showed a significant difference in mental health scores between male and female students (p = 0.045), with women scoring higher. The most prominent tendency of mental disorders in women was tendency of schizophrenia (35.9%), followed by impulsivity, emotional expression, and obsession. Meanwhile, in men, the issues that emerge are impulsivity, emotional instability, and schizophrenic tendencies, although in much lower proportions. Conclusion: There is a statistically significant difference between the mental health scores of male and female students. Keywords: Gender; Mental Health; Psychology Students; Tendency of Mental Disorders.   Pendahuluan: Mahasiswa psikologi merupakan kelompok yang rawan mengalami tekanan emosional dan psikologis, baik karena beban akademik maupun ekspektasi terhadap peran profesional di masa depan. Paparan yang lebih sering pada beragam isu Kesehatan mental dapat berkontribusi pada masalah psikologis mahasiswa. Masuknya informasi yang terus-menerus dapat membuat mahasiswa kewalahan dan kesulitan mengatasinya. Tujuan: Untuk mengidentifikasi profil kesehatan mental mahasiswa psikologi ditinjau dari jenis kelamin serta mendeskripsikan kecenderungan gangguan mental yang muncul pada masing-masing gender. Metode: Penelitian kuantitatif komperatif ini melibatkan 70 mahasiswa psikologi. Pengumpulan data dilakukan menggunakan instrument Woodworth’s Quesionnaire. Data dianalisis menggunakan Independent Samples T-Test untuk melihat perbedaan skor berdasarkan gender dan analisis deksriptif. Hasil: Analisis menunjukkan perbedaan signifikan antara skor kesehatan mental mahasiswa laki-laki dan perempuan (p = 0.045), di mana perempuan menunjukkan skor yang lebih tinggi. Tendensi gangguan mental yang paling menonjol pada perempuan adalah tendensi schizophrenia (35.9%), diikuti oleh impulsivitas, ekspresi emosi, dan obsesi. Sementara pada laki-laki, isu yang muncul adalah impulsivitas, ketidakstabilan emosi, dan tendensi schizophrenia, meskipun dalam proporsi yang jauh lebih rendah. Simpulan: Terdapat perbedaan yang signifikan secara statistik antara skor kesehatan mental mahasiswa laki-laki dan perempuan. Kata Kunci: Gender; Kesehatan Mental; Mahasiswa Psikologi; Tendensi Gangguan Mental.